2018
DOI: 10.1016/j.jsbmb.2017.03.021
|View full text |Cite
|
Sign up to set email alerts
|

Twenty years of the G protein-coupled estrogen receptor GPER: Historical and personal perspectives

Abstract: Estrogens play a critical role in many aspects of physiology, particularly female reproductive function, but also in pathophysiology, and are associated with protection from numerous diseases in premenopausal women. Steroids and the effects of estrogen have been known for ∼90 years, with the first evidence for a receptor for estrogen presented ∼50 years ago. The original ancestral steroid receptor, extending back into evolution more than 500 million years, was likely an estrogen receptor, whereas G protein-cou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
140
1
2

Year Published

2019
2019
2020
2020

Publication Types

Select...
3
2
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 203 publications
(158 citation statements)
references
References 198 publications
0
140
1
2
Order By: Relevance
“…In terms of structure, GPER1 does not share similarities with ERα or ERβ. As a typical G protein coupled receptor, its structure consists of 7 transmembrane α-helical regions, 4 extracellular segments, and 4 cytosolic segments (Barton et al, 2018). This receptor has low binding affinity (17B-estradiol) when compared to other estrogen receptors (Prossnitz & Barton, 2014).…”
Section: Structural Properties Of Estrogen Receptorsmentioning
confidence: 99%
See 1 more Smart Citation
“…In terms of structure, GPER1 does not share similarities with ERα or ERβ. As a typical G protein coupled receptor, its structure consists of 7 transmembrane α-helical regions, 4 extracellular segments, and 4 cytosolic segments (Barton et al, 2018). This receptor has low binding affinity (17B-estradiol) when compared to other estrogen receptors (Prossnitz & Barton, 2014).…”
Section: Structural Properties Of Estrogen Receptorsmentioning
confidence: 99%
“…Both the membrane bound estrogen receptor GPER1, and some variants of the ERα and ERβ have been associated to non-genomic estrogen signaling (Barton et al, 2018; E. J. Filardo & Thomas, 2012).…”
Section: Membrane Receptor: Indirect Non-genomic Signalingmentioning
confidence: 99%
“…A greater proportion of FSHR only complexes would thus program the cell fate toward FSHR/cAMP-dependent death, a finding well described in the literature [5][6][7]9,[55][56][57][58][59] but neglected for a long-time due to the lack of evidence on the pro-apoptotic action of FSH in vivo. Indeed, FSH action is commonly associated with 32 proliferative events, follicular growth being the physiological example, and as suggested by the presence of FSHR in pathological contexts characterized by uncontrolled cell growth, such as cancer 28 or endometriosis 29 , which indicated FSHR as a target of anti-cancer drugs 30 .…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with its impact on cell growth, FSHR expression was found in pathological contexts characterized by uncontrolled cell proliferation, such as tumors 28 or endometriosis 29 , suggesting that it could be a target for still outstanding anti-cancer therapies 30 . Similarly, GPER expression has been described in several tumor cells 31 , including breast, endometrium and ovary 32 , where it may cooperate with FSHR in inducing uncontrolled cell proliferation 27,33 .…”
Section: Introductionmentioning
confidence: 90%
“…GPER was formerly known as the orphan receptor GPR30 until growing evidence suggested that its activity was modulated by endogenous estrogens and estrogenic compounds (Barton et al., ). Evidence included correlating nongenomic estrogen‐mediated signaling events with calcium and cAMP flux, EGFR activity, and the MAPK‐ERK1/2 cascade (Filardo, Quinn, & Frackelton, ; Revankar, Cimino, Sklar, Arterburn, & Prossnitz, ).…”
Section: Commentarymentioning
confidence: 99%